2017
DOI: 10.1099/jmm.0.000641
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary infusion of a live culture of Lactococcus lactis in ewes to treat staphylococcal mastitis

Abstract: Under our experimental conditions, the L. lactis treatment led to a transient clearance of the pathogen in the gland, but also caused mild to moderate clinical cases of mastitis. We believe it is still early to implement bacterial formulations as alternatives in treating mastitis in ruminants and further experimentation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In bovines, intramammary infusion with lactococci has been proposed to be as effective at eliminating chronic subclinical infections as an antibiotic treatment (Klostermann et al, 2008). However, rather than reconstituting the microbiota equilibrium, some authors argue that this might be due to an immune stimulation enabling a response of the mammary gland and clearance of subclinical intramammary infection agents (Crispie et al, 2008;Mignacca et al, 2017). In line with this concept, Pellegrino et al (2017) described that inoculation of lactic acid bacteria in cows at dry-off period increased the amount of IgG isotypes in blood and milk and found that these antibodies were able to recognize S. aureus epitopes.…”
Section: Can We Manipulate the Milk Microbiota In Order To Improve Mamentioning
confidence: 99%
“…In bovines, intramammary infusion with lactococci has been proposed to be as effective at eliminating chronic subclinical infections as an antibiotic treatment (Klostermann et al, 2008). However, rather than reconstituting the microbiota equilibrium, some authors argue that this might be due to an immune stimulation enabling a response of the mammary gland and clearance of subclinical intramammary infection agents (Crispie et al, 2008;Mignacca et al, 2017). In line with this concept, Pellegrino et al (2017) described that inoculation of lactic acid bacteria in cows at dry-off period increased the amount of IgG isotypes in blood and milk and found that these antibodies were able to recognize S. aureus epitopes.…”
Section: Can We Manipulate the Milk Microbiota In Order To Improve Mamentioning
confidence: 99%
“…The cure rates of the two treatments were similar. Two field studies carried out on ewes were used to assess the capacity of the L. lactis LMG7930 to cure staphylococcal (CoNS or S. aureus ) infections ( 106 ). The infused glands developed an inflammatory response, which was accompanied by a transient eclipse in CoNS milk shedding followed by relapse, but no effect on S aureus infections.…”
Section: Appraisal Of Published Probiotic Trials In Relation To Mastimentioning
confidence: 99%
“…In a model of mouse mastitis, the experimental infection with Staphylococcus chromogenes and treatment with live cultures of Lactococcus lactis induced an increased level of IL-1β and TNFα, in addition to tissues damages, suggesting that these GRAS strains cannot be used for mastitis treatment in rodents. Recent findings on ewes affected by subclinical mastitis confirmed that the infusion of Lactococcus lactis into the mammary gland leads to a transient clearance of the pathogens, but also increases the inflammatory status of the mammary gland [24]. Similarly, treatment with different strains of Lactobacillus failed to decrease cow mastitis and caused a local inflammatory response [25,26].…”
Section: Introductionmentioning
confidence: 99%